Comparing the clinical significance and antigen specificity of insulinoma‐associated antigen‐2 autoantibodies between radioimmunoassay and enzyme‐linked immunosorbent assay in Japanese patients with type 1 diabetes. Issue 1 (30th September 2022) - Kawasaki, Eiji; Shimada, Akira; Imagawa, Akihisa; Abiru, Norio; Awata, Takuya; Oikawa, Yoichi; Osawa, Haruhiko; Kawabata, Yumiko; Kozawa, Junji; Kobayashi, Tetsuro; Takahashi, Kazuma; Chujo, Daisuke; et al.
Abstract: Aims/Introduction: This study aimed to investigate the clinical significance and antigen specificity of autoantibodies to insulinoma‐associated antigen‐2 (IA‐2A) by radioimmunoassay (RIA; IA‐2A‐RIA) and enzyme‐linked immunosorbent assay (ELISA; IA‐2A‐ELISA) in Japanese patients with type 1 diabetes. Materials and Methods: A total of 338 type 1 diabetic patients were enrolled, including 38 fulminant type 1 diabetes, 168 acute‐onset type 1 diabetes and 137 slowly‐progressive type 1 diabetes (SPIDDM). The concordance, correlation of autoantibody titer, and the relationship between IA‐2A and progression to the insulin‐deficient state were examined. Also, competitive assay was used to examine the antigen specificity. Results: The prevalence of IA‐2A‐ELISA was 4–5% lower than that of IA‐2A‐RIA in both the acute‐onset type 1 diabetes and SPIDDM, but the diagnostic sensitivities of both subtypes, when measured in combination with glutamic acid decarboxylase autoantibody, were comparable. The diagnosis of type 1 diabetes using either the RIA or ELISA methods showed substantial agreement with the exponential correlation of autoantibody titers detected by RIA and ELISA. Among the SPIDDM patients, the fasting C‐peptide for IA‐2A‐positive cases by ELISA, but not the RIA method, was significantly lower than in the negative cases ( P < 0.05). Furthermore, IA‐2A‐ELISA proved superior to the RIA method in predicting the progression to insulin deficiency in SPIDDM. Competitive analysis showed that even sera with discrepant results by RIA and ELISA have IA‐2‐specific autoantibodies. Conclusion: These results suggest that IA‐2A‐ELISA is a reliable marker not only for the diagnosis of type 1 diabetes, but also for the prediction of future insulin dependency; that is, detection of IA‐2A‐ELISA helps identify a subtype of SPIDDM patients who would likely progress onto insulin‐deficient state. Abstract : In the present study, we showed that the agreement between radioimmunoassay (RIA) and enzyme‐linked immunosorbent assay (ELISA) for insulinoma‐associated antigen‐2 autoantibodies (IA‐2A) by the RSR Ltd. (Cardiff, UK) was 94.7% (κ statistic = 0.000, 95% confidence interval 0.000–0.000) for fulminant type 1 diabetes, 89.3% (κ statistic = 0.786, 95% confidence interval 0.693–0.879) for acute‐onset type 1 diabetes and 90.5% for slowly‐progressive type 1 diabetes (κ statistic = 0.769, 95% confidence interval 0.651–0.888), and the diagnostic sensitivities of autoimmune‐mediated type 1 diabetes when measured in combination with glutamic acid decarboxylase autoantibody were comparable between the RIA and ELISA methods. Furthermore, we reported that RSR IA‐2A‐ELISA is more useful than RSR IA‐2A‐RIA in identifying the subtype of slowly‐progressive type 1 diabetic patients who would likely progress onto an insulin‐deficient state.